City Energy Efficiency Report : Transport Sector Wuhan - Qu, Li; Ardila Gomez, Arturo; Frame, G.; Chen, Yang (World Bank, Washington, DC, 2016)
As a result of rapid development, cities in China are experiencing everincreasing levels of energy consumption that is forcing them to consider and plan their development in a sustainable manner. Transport, one of the most energy dependent sectors, accounted for 37 percent of petroleum consumption in China in 2013. Wuhan is a rapidly growing metropolitan area. Amid extensive construction of infrastructure and ongoing development, the city is seeking strategies to achieve optimal energy efficiency. The World Bank team analyzed energy efficiency across the city, including in the transport sector.